2016
DOI: 10.1016/j.jstrokecerebrovasdis.2015.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone and Subclinical Cerebrovascular Disease: The Atherosclerosis Risk in Communities Brain Magnetic Resonance Imaging Study

Abstract: Background Elevated parathyroid hormone (PTH) levels have been associated with cardiovascular disease risk factors and events. We hypothesized that elevated PTH would also be associated with subclinical cerebrovascular disease. We examined the relationship of elevated PTH with white matter hyperintensities (WMH) and subclinical infarcts measured on brain MRI. Methods PTH was measured at baseline (1993–1994) among participants free of prior clinical stroke who underwent a brain MRI at baseline (n=1703) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…27 We also examined a shorter time frame in a sensitivity analysis, but we did not discover a significant relationship between elevated PTH levels and 6-year cognitive decline. Our results are similar to previous null results from the ARIC Brain MRI Study which showed that PTH was not independently associated with subclinical brain infarcts or white matter hyperintensities on brain MRI, 25 which are indicators for subclinical cerebrovascular diseases and linked with reduced cognitive function. 28 Our findings were also in accordance with another ARIC study that did not show a significant association between PTH and clinical cardiovascular events.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…27 We also examined a shorter time frame in a sensitivity analysis, but we did not discover a significant relationship between elevated PTH levels and 6-year cognitive decline. Our results are similar to previous null results from the ARIC Brain MRI Study which showed that PTH was not independently associated with subclinical brain infarcts or white matter hyperintensities on brain MRI, 25 which are indicators for subclinical cerebrovascular diseases and linked with reduced cognitive function. 28 Our findings were also in accordance with another ARIC study that did not show a significant association between PTH and clinical cardiovascular events.…”
Section: Resultssupporting
confidence: 91%
“…We found previously that those with elevated PTH levels had increased CVD risk factors and were less likely to return for the follow-up study. 25 Therefore, for our prospective analysis, we imputed missing covariates and cognitive data with the multiple imputation by chained equation methods 26 to account for attrition (see table e-2 for numbers imputed).…”
mentioning
confidence: 99%
“…White matter hyperintensities of presumed vascular origin are a common finding in brain MRI or CT 8 scans in older subjects and stroke patients, and are associated with a three times higher risk of stroke. However, these authors did not find an association between elevated PTH level and progression of cerebrovascular changes in brain MRI over a 10-year interval [24]. A longitudinal study of HD patients in the Japan Renal Data Registry found that hemorrhagic stroke was associated with PTH concentration > 500 pg/ml, whereas the incidence of ischemic stroke was unrelated to PTH level [25].…”
Section: Discussionmentioning
confidence: 92%
“…After adjusting for demographic and life style factors, a one year cross-sectional study refuted the relationship between elevated PTH levels and subclinical cerebrovascular disease. 18 Other studies have shown that primary hyperparathyroidism with elevating PTH and significantly increasing blood pressure heightened the risk of female cerebral infarction but had no effect on males. After parathyroidectomy, blood pressure was reduced to normal levels and the risk of stroke decreased.…”
Section: Discussionmentioning
confidence: 99%